Management of Knowledge Transfer for Capacity Building in Africa - Hatcheu, Emil Tchawe (Journal of Comparative International Management, 2017)
Between sporadic remittances and training of a qualified manpower mastering new technologies, what does Africa expect from its diaspora to fill its development gap in the current context of globalization? When it comes to capital building, defined as the process or strategy to endow or increase the technical, managerial, or intellectual skills of an individual or a group, its know-how or knowledge, and financial capital or purchasing power, the World Bank and other development partners seem to grant priority to remittances. This paper strongly suggests that attention may be granted to the transfer of scientific knowledge between Africa and its diaspora, as many believe that progressing knowledge would help bring out a neglected source of wealth to fight the scourges responsible for political and economic backwardness in industrial countries. The development models based on the diaspora’s contribution in several countries and regions of the world, particularly in Asia, show the importance of knowledge transfer in capacity building. Similarly, Silicon Valley in California demonstrates the role of emigrants in the knowledge industry. As the brain drain is a normal phenomenon of globalization, emigration of African professionals is no more an obstacle to Africa’s development. Rather, the African diaspora constitutes a pool of human and investment capital that can strongly contribute to the continent’s development. From our point of view, the diaspora has an important role to play in capacity building, provided respective governments come up with sound policies to promote its participation. The diaspora’s participation in nation-building without physical relocation on the one hand, and the existence of the first generation of retired researchers and academics organized into civil society associations such as AED (Association for Education and Development) in Cameroon, on the other hand, constitute the pipeline of knowledge transmission. African partners and its diaspora can build a genuine partnership to create sustainable and competitive scientific institutions in Africa on this foundation. Improved governance, leadership, regulations, and immigration policy of sending and receiving countries are necessary for transnational scholarly/economic engagement.